The concept of sustainability from the Islamic perspectives - Ahmad Sarkawi, Azila; Abdullah, Alias; Md Dali, Norimah (International Journal of Business, Economics and Law (IJBEL), 2016)
Muslims are religiously entrusted to prosper the earth via performing their obligations as khalifah (vicegerent). Indeed their performance will be queried in the Day of Resurrection. Since the 80s when the concept of ‘sustainability’ was first introduced, this term had been persistently centred on the context of renewable resources and ecological capabilities to support human life. At this juncture, it is worth considering shifting the paradigm to include the Islamic point of view especially pertaining to the built environment professions. Thus, this paper is reviewing the present concept of sustainability including the positioning of its three pillars namely environment, social and economy from the Islamic perspectives.